Thực trạng hoạt động giáo dục kĩ năng mềm cho học sinh ở Trường Trung cấp Miền Nam, tỉnh Bình Phước - Lê, Văn Lợi; Nguyễn, Thị Ngọc Bé (Tạp chí Giáo dục, 2025)
Soft skills education is essential in preparing students for a successful and happy future. In addition to providing academic knowledge, equipping students with soft skills will help them develop comprehensively and respond flexibly to life and work challenges. Incorporating soft skills education into the school curriculum is an urgent requirement in the current context. The article analyzes and clarifies the current status of soft skills education activities for students at Southern Vocational School, Binh Phuoc province. Based on the investigation method of 50 managers, teachers, and 320 students, the survey results show that soft skills education activities have been interesting and implemented, bringing about some encouraging results. However, the effectiveness of these activities has not yet reached the optimal level and has not fully exploited the potential of students. The research results will be an essential practical basis for proposing measures to improve the effectiveness of soft skills education for students.